The Application Path of the Rule of Presumption of Evidence in Maritime Administrative Cases: Analysis of Article 35 of the Coast Guard Law - Zhang, Zheng (International Journal of Social Sciences and Public Administration, 2024)
Article 35 of the Coast Guard Law of the People’s Republic of China stipulates the rules for presumption of evidence in handling maritime administrative cases, which is a clear legal provision for the reversal of the burden of proof. The parties involved need to bear the complete burden of proof. In the specific application of administrative cases, maritime police agencies should strictly focus on the three basic elements of the presumption basis, basic facts, and illegal facts of the evidence presumption rule. Article 35 of the Maritime Police Law is both a presumption basis and a judicial norm. Maritime police agencies need to bear the burden of proof for the basic facts of the destruction of evidence by the parties. After reaching the standard of proof that eliminates reasonable suspicion, they can infer that the parties have violated the law. At the same time, in order to safeguard their legitimate rights and interests, the parties may refute the basic facts claimed by the maritime police agency or prove that the presumed facts of the maritime police agency are incorrect, but they do not demand a higher standard of proof for the basic facts than the maritime police agency.